Analysis of Carbon Storage in Coastal Salt Marsh Ecosystem in Hebei Province - LYU Hongjuan; FAN Qianying; ZHANG Songyue (Haiyang Kaifa yu guanli)
Coastal salt marshes are located in the transition area between sea and land, affected by periodic or intermittent ocean tides and covered with herbous or low shrubs. They are an important part of coastal wetlands and an important carbon sink area, making an important contribution to the global carbon sink. The study area includes the coastal wetlands of Qinhuangdao, Tangshan and Cangzhou in Hebei Province. The distribution characteristics of coastal salt marsh in Hebei Province were determined by remote sensing identification and on-site verification, and the characteristics of salt marsh plant communities were studied and analyzed. The vegetation types were spartina alterniflora, reed and saltmarsh, and the total distribution area was 444.99 hm2. In this study, 79 stations were collected, 158 biological samples and 474 sediment samples were collected. The aboveground biomass, underground biomass, organic carbon and sediment carbon reserves and their influencing factors of coastal salt marsh in Hebei Province were analyzed. Based on the calculation results of vegetation carbon bank and sediment carbon bank at all monitoring stations of different salt marsh vegetation types, the average vegetation carbon density in Spartina alterniflora distribution area was 3.80Mg C/hm2, that in saltland bordus distribution area was 0.96Mg C/hm2, and that in reed distribution area was 2.99Mg C/hm2. According to the regional calculation, the total carbon storage of salt marsh ecosystem in Hebei Province is (2.11±0.17) thousand t. The research results reveal the organic carbon content and carbon storage characteristics of salt marshes in coastal zone of Hebei Province, which can provide basic data for the assessment of carbon sink capacity of salt marshes and restoration of degraded salt marsh wetlands in Hebei Province in the future.